TRANSLATORS AND TRANSLATIONS OF K. DONELAITIS INTO LATVIAN: THE SECOND HALF OF THE 19TH–20TH CENTURIES - ZANDERS, VIESTURS (Knygotyra, 2015)
It took quite a long time for the poem `The Seasons” by Kristijonas Donelaitis to have a full translation in Latvian – up to the second half of the 20th century. The first translation – some fragments of the poem – were made by a pastor in Kurzeme, Carl Friedrich Watson, and published in the twenties of the 19th century. The first thorough publication about K. Donelaitis himself was written by Andrejs Dīriķis (in 1874) who regularly covered Lithuanian culture in Latvian press in the seventies and eighties of the 19th century. The translation of “The Seasons” made by the Latvian poet Rainis in the eighties of the 19th century unfortunately has not survived. In the thirties and forties of the 20th century the translation of the poem was initiated by the writer and promoter of Latvian – Lithuanian cultural ties Emīls Skujenieks. In 1963 and 2006 two different versions of translation made by the poet Paulis Kalva were published. The recent publications of comparative literary studines give us evidence, that further research of the translations in Latvian of the Donelaitis poem, especially using new sources, is rather promising.